Effect of sampling effort on taxa richness of aquatic macroinvertebrates and the BMWP/Atitlán index - Reyes-Morales, Fátima (2014)
Aquatic macroinvertebrates are the group of organisms most commonly used to determine ecosystem health in water quality studies and freshwater biomonitoring. Nevertheless, the methods and collecting time of biomonitoring have not yet been sufficiently adapted and tested in tropical aquatic environments. Twelve rivers in the Lago de Atitlán watershed in Guatemala were assessed with different collecting times, during the dry season. The method involved the collection of organic and inorganic material including benthic organisms, from different microhabitats, for a pre-established time period (5, 10, 15min) with a D-frame net. Samples were preserved with 95% ethanol in the field, and sorted in the laboratory. As expected, the analysis showed that the abundance and taxonomic richness was higher with increasing sampling effort. The water quality categories obtained from the newly proposed BMWP/Atitlán index varied among sampling times. However, the Kruskal-Wallis test showed no significant differences between the categories obtained with the index and the number of taxa collected at 10 and 15min. Therefore, we recommend a reduction of sample time, but maintaining the tree subsamples in order to include most variety of microhabitats and assure a representative sample of the aquatic macroinvertebrates. Rev. Biol. Trop. 62 (Suppl. 2): 291-301. Epub 2014 April 01.